Common and distinct circulating microRNAs in four neurovascular disorders - Koskimäki, Janne; Jhaveri, Aditya; Srinath, Abhinav; Bindal, Akash; Cruz, Diana Vera; Yeradoddi, Geetha Priyanka; Lightle, Rhonda; Lee, Justine; Stadnik, Agnieszka; Iqbal, Javed; Alcazar-Felix, Roberto; Hage, Stephanie; et al. (Elsevier BV, 2026)
Background: Familial cerebral cavernous malformations (FCCM), Sturge-Weber Syndrome (SWS), and hereditary hemorrhagic telangiectasia (HHT) are driven by genetic mutations causing varying vascular dysmorphism and risk of brain bleeding. Cerebral microbleeds (CMBs) are associated with the aging process with less characterized genetic drivers. This study hypothesizes that common and distinct circulating microRNAs (miRNAs) can reflect mechanisms of vascular dysmorphism and bleeding, which can serve as potential biomarkers in clinical contexts.
Methods: Differentially expressed (DE) plasma miRNAs (p < 0.05, FDR corrected, absolute fold change [|FC|]>1.5]) were identified between patients with FCCM, SWS, HHT, and CMB, compared to age and sex matched healthy patients. Ingenuity Pathway Analysis as well as transcriptome integration analyses were performed to identify gene targets of the DE miRNAs and their associated pathways. Preselected miRNAs were validated using ddPCR.
Results: Eleven circulating DE miRNAs were identified in FCCM, 40 in SWS, 41 in HHT, and 26 in CMB (p < 0.05, FDR-corrected, [|FC|]>1.5]). Further analyses showed that 18 DE miRNAs were commonly dysregulated in any two of the studied neurovascular disorders. The PI3K-Akt and ROBO SLIT signaling pathways were identified across all four disorders. The plasma levels of four miRNAs were further validated (p < 0.05) using ddPCR.
Conclusion: The common dysregulated miRNAs across neurovascular disorders reflect shared mechanistic pathways underlying vascular dysmorphism and bleeding. These findings pave the way for further mechanistic exploration of these miRNAs, and their potential clinical application for disease monitoring and therapeutic intervention.